IMPLEMENTATION OF CLOUD COMPUTING IN THE DEVELOPMENT OF DISTRIBUTED COMPUTER SYSTEMS - Saputra, Memed; Jonathan, Davy; Aribowo, Aribowo (Yayasan Adra Karima Hubbi, 2025)
The rapid evolution of information technology has driven a significant shift from centralized to distributed computing architectures. One of the most transformative innovations in this domain is cloud computing, which offers scalable, flexible, and cost-effective solutions for managing large-scale distributed systems. This study investigates the implementation of cloud computing in the development of distributed computer systems, focusing on its impact on performance, resource utilization, and system scalability. The objective of this research is to analyze the effectiveness of cloud-based infrastructures in supporting distributed applications and to identify best practices for optimizing system architecture within a cloud environment. A mixed-method approach was employed, combining qualitative system analysis with quantitative performance metrics derived from cloud-deployed prototypes. Various case studies across different sectors—education, healthcare, and business—were used to illustrate real-world applications. The findings reveal that cloud computing significantly enhances the operational efficiency and adaptability of distributed systems. Key improvements include dynamic resource allocation, simplified maintenance, and increased fault tolerance. In conclusion, the integration of cloud computing into distributed systems presents a robust framework for modern computing needs. It not only reduces operational complexity but also facilitates innovation by enabling seamless scalability and rapid deployment. Future research is encouraged to explore hybrid cloud models and edge computing integration to further enhance distributed system performance in latency-sensitive environments.